Fill Removal with Foam in Horizontal Well Cleaning in Coiled Tubing - Khan, Javed A (2013)
Coiled Tubing (CT) services are extensively used in oil industry to clean out the fill produced from wellbore. Recently, the use of foam as cleaning agent has become more popular due to its low density and high viscosity which are desirable in many cleaning operations. The present study is carried out to investigate the suspension of fines in the annulus of CT during cleaning operations. Solid particles were uniformly injected at annulus inlet and sand concentration at each point in the annular was calculated along the horizontal wellbore section. The motion of the particles is calculated under the effect of drag, buoyancy, rotational and virtual mass forces to analyze the settlement of the particles. The foam quality and foam velocity are found to be the deciding factors for the particle depositional pattern. The fill removal efficiency and frictional pressure loss are affected by both the velocity of the annular flow and the quality of the foam.